Risk of readmission to the emergency department in mild COVID-19 outpatients with telehealth follow-up - Pedretti, Ana; Marquez Fosser, Santiago; Pasquinelli, Rosario; Vallone, Marcelo; Plazzotta, Fernando; Luna, Daniel; Martínez, Bernardo; Rodríguez, Paz; Grande Ratti, María Florencia (2021)
Fil: Pedretti Ana. Hospital Italiano de Buenos Aires; Argentina.